Active Learning Strategy to Improve Students’ Science Learning Outcomes: Strategi Pembelajaran Aktif untuk Meningkatkan Hasil Pembelajaran Sains Siswa - Novianti, Intan Auliya; Nastiti, Dwi (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Science learning requires active engagement to help students understand abstract concepts effectively. Specific Background: Many students still struggle to achieve optimal results when taught using conventional methods. Knowledge Gap: Few studies explore the application of this learning method in the selected science topic at the given educational level. Aim: This research aims to analyze the improvement of students’ learning outcomes through the implementation of the selected active learning strategy. Results: The findings indicate a significant increase in students’ post-test scores compared to pre-test scores, confirming the method’s ability to support better comprehension. Novelty: This study introduces the integration of the chosen active learning method in a science topic rarely studied in this context. Implications: The results suggest that teachers can adopt this approach as a model for designing engaging and effective science lessons. 10. Highlight & Keyword Highlight Active learning improves science achievement Pre-test and post-test results show clear improvement Supports future lesson planning Keyword: Active Learning, Science Education, Learning Outcomes, Classroom Strategy, Student Engagement